2009
DOI: 10.1063/1.3126522
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic design of GaInNAs quantum well laser diodes on ternary substrates for high-speed and high-temperature operations

Abstract: Articles you may be interested inDesign and modeling of InP-based InGaAs/GaAsSb type-II "W" type quantum wells for mid-Infrared laser applications J. Appl. Phys. 113, 043112 (2013); 10.1063/1.4789634Theoretical study of Auger recombination in a GaInNAs 1.3μ m quantum well laser structure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Although FCT is easy to use for obtaining optical properties of QWs, it needs an experimental fitting parameter (relaxation time) associated with optical spectrum broadening originating from scattering phenomena in semiconductors. Results obtained by FCT are greatly affected by the fitting parameter (shown later), and it was demonstrated that spectral positions and the spectral shapes obtained by FCT are not consistent with the experiment [10][11][12][13][14]. Therefore, it is difficult to grasp the inherent optical properties of GeSn QWs if FCT is used for the analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although FCT is easy to use for obtaining optical properties of QWs, it needs an experimental fitting parameter (relaxation time) associated with optical spectrum broadening originating from scattering phenomena in semiconductors. Results obtained by FCT are greatly affected by the fitting parameter (shown later), and it was demonstrated that spectral positions and the spectral shapes obtained by FCT are not consistent with the experiment [10][11][12][13][14]. Therefore, it is difficult to grasp the inherent optical properties of GeSn QWs if FCT is used for the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the material gain of GeSn/SiGeSn QWs is investigated for mid-IR Si-photonics light sources by using microscopic many-body theory (MBT) [10][11][12][13][14][15]. MBT does not need any fitting parameters used in FCT to obtain optical properties of QWs and only needs basic bulk band parameters.…”
Section: Introductionmentioning
confidence: 99%